Parental social anxiety disorder prospectively predicts toddlers' fear/avoidance in a social referencing paradigm. (2nd August 2013) - Aktar, Evin; Majdandžić, Mirjana; de, Wieke; Bögels, Susan M.
<x xml:space="preserve">Abstract</x> Background Anxiety runs in families. Observational learning of anxious behavior from parents with anxiety disorders plays an important role in the intergenerational transmission of anxiety. We investigated the link between parental anxiety (parental lifetime anxiety disorders and expressed parental anxiety) and toddler fear/avoidance during social referencing (SR) situations. Method Toddlers (N = 117) participated with both parents (with lifetime social anxiety disorder, other nonsocial anxiety disorders, lifetime comorbid social and other anxiety disorders, or without anxiety disorders) in a longitudinal study. Behavioral inhibition (BI) was measured at 12 months via observational tasks. At 30 months, children were confronted with a stranger and a remote‐control robot in SR situations, separately with each parent. Children's fear and avoidance, and parents' expressions of anxiety, encouragement, and overcontrol were observed. Results Toddlers of parents with lifetime social anxiety disorder (alone and comorbid with other anxiety disorders) showed more fear/avoidance in SR situations than toddlers of parents without anxiety disorders, while the effect of other anxiety disorders alone was not significant. Although expressed parental anxiety at 30 months in SR situations did not significantly predict toddlers' fear/avoidance, higher levels of expressed anxiety at 12 months in SR situations by parents with comorbid social and other anxiety disorders predicted higher levels of fear/avoidance. BI at 12 months predicted toddlers' fear/avoidance only with mothers, but not with fathers. Conclusions Parental lifetime social anxiety disorders may be a stronger predictor of children's fear/avoidance than parents' expressions of anxiety in SR situations in toddlerhood. End of infancy may be a sensitive time for learning of anxiety from parents with comorbid lifetime social and nonsocial anxiety disorders in SR situations. Fathers are as important as mothers in the transmission of anxiety via SR. Furthermore, children may act relatively free of their early temperament in SR situations with fathers.